2019
DOI: 10.3389/fnins.2019.01135
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in 48 Genes Account for 42% of Cases of Epilepsy With or Without Neurodevelopmental Delay in 246 Pediatric Patients

Abstract: In order to characterize the genetic architecture of epilepsy in a pediatric population from the Iberian Peninsula (including the Canary Islands), we conducted targeted exome sequencing of 246 patients with infantile-onset seizures with or without neurodevelopmental delay. We detected 107 variants in 48 different genes, which were implicated in neuronal excitability, neurodevelopment, synaptic transmission, and metabolic pathways. In 104 cases (42%) we detected variant(s) that we classified as pathogenic or li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 88 publications
1
29
0
Order By: Relevance
“…We found that about three-quarters of this burden was in known DD genes. These proportions are similar to findings in other exome-sequencing studies of similar cohorts [39][40][41] . For example, in one of the largest comparable studies, 34/938 (3.6% [2.5%-5.0%]) male probands and 29/728 (4.0% [2.7%-5.7%]) female probands with neurological disorders had a diagnostic X-linked variant 41 , versus 3.8% and 5.4% respectively in DDD (inferred from burden analysis in known DD-associated genes).…”
Section: Discussionsupporting
confidence: 90%
“…We found that about three-quarters of this burden was in known DD genes. These proportions are similar to findings in other exome-sequencing studies of similar cohorts [39][40][41] . For example, in one of the largest comparable studies, 34/938 (3.6% [2.5%-5.0%]) male probands and 29/728 (4.0% [2.7%-5.7%]) female probands with neurological disorders had a diagnostic X-linked variant 41 , versus 3.8% and 5.4% respectively in DDD (inferred from burden analysis in known DD-associated genes).…”
Section: Discussionsupporting
confidence: 90%
“…To investigate the impact of Wwox deficiency on human brain developmental processes, we performed brain histopathological analyses of the 21th week aborted fetus (II.3) with WOREE syndrome and identified abnormal architecture of the developing cerebral cortex. Development of the cerebral cortex is a very dynamic and highly organized process, involving a series of complex morphogenetic events, which can be impaired in different neurodevelopmental disorders (Fernández-Marmiesse et al, 2019;Seto and Eiraku, 2019;Magdalon et al, 2020). Following division of progenitor cells in the ventricular zone, neurons undergo several physiological changes and migrate outward toward the cortical plate, where they differentiate and integrate into functional neural circuits (Romero et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since Garcia CC et al rstly connected SYN1 mutation with neurodevelopmental disorder in 2004, 16 causative variants including ten missense mutations, ve nonsense mutations, and one splicing site mutation in the gene have been identi ed (containing this study) (Fig. 2) [1,2,[7][8][9][10][11][12][13][14][15][16]. These variants are clustered in B linker domain (A51G, S79W), actin-binding and synaptic-vesicle binding C-domain (W126X, W126R, c.527+1G>A, S212I, G240R, V266M, W356X, T359K, R420G) and proline-rich D-domain (R422X, Q482X, A550T, Q555X, T567A) of the encoded protein as indicated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the clinical characteristics of SYN1-related disorder, we conducted a literature review of all reported pedigrees from the Pubmed and Embase on English articles. Clinical information of 7 pedigrees with the disorder from 7 studies was collected in the report (Table 1) [2,[9][10][11][12][13][14], and other cases were excluded for lack of detail descriptions [1,7,8,15,16]. Overall, we noticed that females are less susceptible than males due to X-chromosome random inactivation (XCI), however, few female carriers presented with mild intellectual disability and febrile seizures [8,14].…”
Section: Discussionmentioning
confidence: 99%